1989
DOI: 10.1080/01688638908400925
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive writing abilities in Alzheimer's disease

Abstract: The descriptive writing abilities of 15 subjects with Alzheimer's disease (AD) of mild to moderate severity were compared with 15 age- and sex-matched normal controls. Sixteen features of written linguistic ability were analyzed. AD subjects wrote shorter descriptive paragraphs than normal elderly subjects. Features related to letter or spelling errors and content words were found to be significantly different between the two groups, whereas functor word errors and number of attempted corrections did not signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 5 publications
3
18
0
1
Order By: Relevance
“…They were also characterized by some misspellings. At the syntactic level, AD patients produced fewer and shorter clauses, especially subordinate clauses, as well as fewer verbs, prepositions, and conjunctions, whereas their number of grammatical errors was comparable to that of controls [10,13,14]. The analysis of single written sentences confirmed that written syntax was simplified but always coherent [15].…”
Section: Written Description Of a Complex Picturesupporting
confidence: 49%
“…They were also characterized by some misspellings. At the syntactic level, AD patients produced fewer and shorter clauses, especially subordinate clauses, as well as fewer verbs, prepositions, and conjunctions, whereas their number of grammatical errors was comparable to that of controls [10,13,14]. The analysis of single written sentences confirmed that written syntax was simplified but always coherent [15].…”
Section: Written Description Of a Complex Picturesupporting
confidence: 49%
“…The shortest sentences were written by patients with dementia, those with MCI wrote slightly longer sentences, and the longest sentences were written by patients without cognitive impairment. This result was expected and coincides with that of previous studies, confirming that the ability to write a sentence is adversely affected by cognitive impairment [3,6,27]. A previous study found a correlation between the degree of cognitive impairment and a decline in the ability for sentence writing: while 85% of nondemented elderly wrote a correct spontaneous sentence, only 67% of those with mild dementia, 41% of those with moderate dementia and none with severe dementia were able to write such a sentence [29].…”
Section: Discussionsupporting
confidence: 81%
“…In a study of patients with AD, the ability to formulate a complete sentence was related to dementia severity [5]. When asked to write a story about a picture, patients with AD of mild to moderate severity wrote shorter descriptive paragraphs than normal subjects matched for age and gender (28.4 vs. 79.9 words) [6]. …”
Section: Introductionmentioning
confidence: 99%
“…A positive correlation was observed between the severity of the dementia and spelling/writing measures (lexical and allographic). Agraphia or dysgraphia, observed in early AD [22], encompasses a progressive disorganization and degeneration of the various components of handwriting [23]; these include the complexity of the structure of sentences [24], the diversity and the accuracy of words used [25], punctuation [26], organization [25], the production of grammatically incorrect sentences [27,28], the length of the sentences [27], the amount of written information [28], the morphology of the letters [27] and spelling [29], graphic and spatial layout of letters and their arrangement in texts [18]. Fukui and Lee [30] examined the possibility that agraphia/dysgraphia may be an early sign of degenerative dementia, reporting the concurrent or subsequent emergence of non-fluent aphasia, ideomotor apraxia, executive dysfunction and asymmetric akinesicrigid syndrome; these observations implicate degenerative processes involving the parietal-occipital-temporal regions, basal ganglia and striato-frontal projections.…”
Section: Introductionmentioning
confidence: 99%